A leakage correction with SPH factors for two-group constants in GET-based pin-by-pin reactor analyses. (July 2019) - Yu, Hwanyeal; Kim, Woosong; Kim, Yonghee
Highlights: To improve accuracy of two-step pin-wise core analyses, a GPS (GET plus SPH) has been developed. XS-dependent SPH factors are functionalized with a pin-wise leakage information. Regardless of cores size and FA loading pattern, the GPS method improves significantly accuracy of pin-wise PWR analyses. Abstract: In this paper, a new leakage correction method called GET plus SPH (GPS) method is introduced. First, both GET-based and SPH-based two-step pin-by-pin methods are applied to a small PWR benchmark to evaluate their limited accuracy. In order to improve the accuracy in the two-step method, we introduced the cross-section (XS) dependent SPH factors, which are parameterized as a function of the integrated pin-wise albedo information, i.e., current-to-flux ratio (CFR). For the functionalization of the XS-dependent SPH factor, small color-set problems are modeled to obtain the relationship between the CFR information and the SPH factors. The color-set problems are comprised of several fuel assemblies (FAs) to obtain physically meaningful perturbations in pin-wise CFR values relative to the single-assembly CFR values. The GPS functions are separately determined for each region in FA to consider their position-dependent characteristics. In this work, both the color-sets and whole core problems are solved by the DeCART2D code, which is a 2-D method of characteristic based lattice code. The GPS method is implemented to an in-house pin-wise diffusion analyzer based on a pin-wise CMFD method. To test the performance of the GPS method, a small PWR benchmark is considered in this study. In addition, the same GPS functions are applied to its small and large variants to demonstrate that the GPS functions can be reliably utilized regardless of the different core configurations. The results of this work show that the GPS method can improve substantially the accuracy of the pin-wise reactor analyses with a small additional computational cost.